REVISUALISASI AKSARA KAGANGA SEBAGAI IDENTITAS LAMPUNG - Arif Budiman; PG. Wisnu Wijaya; Muhammad Hajid An Nur; Maria Veronika Halawa; Susi Susyanti (Jurnal Bahasa Rupa, 2019)
The research and design of the Kaganga Script Revisualization as Lampung Identity or Had Lampung is an attempt to provide aesthetic value to the conventional letter system. The aesthetic aspects that were given derived from Lampung cultural traditions, icons, and other visual idioms, such as ornaments on tapis cloth, carvings, traditional clothing accessories, and the stylization of Lampung's unique flora and fauna. The research method of the Kaganga script re-visualization is using Creative Thinking Process approach of Bryan Lawson, who applies steps in solving visual communication problems through several stages; (1) initial understanding (2) preparation (3) incubation (4) information (5) verification. Data analysis is done by considering several aesthetics factors; legibility, readability and unity. From several design or prototype alternatives that have been tested, the new Kaganga script using the Jungian (ship) motif was selected. This design uses Lampung traditional idioms to stylize the original script, which are the stylization of the Jung / Ship motif and the motif of Gold Thread Embroidery. Furthermore, this design can be continued on to the public testing and introduce it to Lampung public after it has been digitized.